Diversidad taxonómica de lagartijas (Squamata: Lacertilia) asociada a cuatro tipos de vegetación de la sierra El Cuale, Jalisco, México - Peña-Joya, Karen Elizabeth; Téllez-López, Jorge; Rodríguez-Zaragoza, Fabián Alejandro; Rodríguez-Troncoso, Alma Paola; Quijas, Sandra; Cupul-Magaña, Fabio Germán (Instituto de Ecología, A.C., 2018)
The lizard composition and diversity of lizards fauna are influenced by vegetation types, because these determine the physical and environmental structure of their habitats. The aim of this study was to determine and analyze the taxonomic diversity of lizards from Sierra El Cuale conservation priority area in Jalisco, Mexico, associated with four vegetation types: tropical semideciduous forest (BT), oak forest (BE), pine-oak forest (BPE), and pine forest (BP). Monthly sampling was carried out from July 2015 to June 2016. A total richness of 12 species was recorded in the study area: nine species in BE, eight in BT, six in BPE, and six in BP. The species accumulation curves showed that more sampling effort is required to characterize the lizard community as a whole. The species Anolis nebulosus, Sceloporus melanorhinus, and S. utiformis were observed in the four types of vegetation, but Basiliscus vittatus, Gerrhonotus liocephalus, and Scincella assatus only in one each. A nonmetric multidimensional scaling analysis (NMDS) identified two groups according to the presence of lizard species and seasons (rainy and dry): BPE-BP, and BT-BE. The average taxonomic distinctness (Δ+) and the species richness were high in the rainy season. The results of this study show that the lizard species richness in Sierra El Cuale is linked to vegetation type variety. On the other hand, the comparative analysis of Δ+ between Sierra El Cuale and Biosphere Reserves of Chamela-Cuixmala and Manantlán, showed that Sierra El Cuale has an important role in the contribution of regional lizard diversity.